From past to future: understanding and accounting for recruitment variability of Australia's redleg banana prawn (Penaeus indicus) fishery. (11th June 2020) - Plagányi, Éva; Deng, Roy Aijun; Hutton, Trevor; Kenyon, Rob; Lawrence, Emma; Upston, Judy; Miller, Margaret; Moeseneder, Chris; Pascoe, Sean; Blamey, Laura; Eves, Stephen
Abstract: Understanding recruitment variability in marine fisheries has benefits for the stock management and dependent fishers' ability to plan their income. Here, we overview past and new research on the complex recruitment dynamics of redleg banana prawns Penaeus indicus in Australia's Joseph Bonaparte Gulf to assess themes dating back to the time of Hjort and identify new challenges. During 2015 and 2016, redleg prawn catches and catch per unit effort decreased to anomalously low levels, suggesting a substantial decrease in prawn biomass. We hypothesized that low catches could be explained by temporary drops in sea level and rainfall potentially reducing the ability of postlarvae to reach their nursery ground. We contend that very bad prawn catch years may be predicted using two variables that are possible drivers of recruitment—the January Southern Oscillation Index and the combined January to February cumulative rainfall. However, due to challenges in verifying and defining such environmental relationships for inclusion in a stock assessment, we propose development of a harvest strategy framework to support management recommendations. Our study highlights the increasing role of anthropogenic climate change in exaggerating the impacts of environmental drivers on recruitment processes and the need to also focus on multidisciplinary research.